Membedah Tindak Pidana Politik Uang, Suatu Telaah Dari Sisi Struktur Norma - Muammar, Muammar; Taufik, Iqbal (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: Money politics is one of the crimes regulated in the Election Law. This crime in the Election Law regime is considered a Structured, Systematic and Massive Crime (TSM). This crime has always been a discourse that surfaced in the public when approaching elections / elections. Especially now, Indonesia is undergoing a political year leading to the upcoming 2024 elections. Purpose of the Research: this paper aims to dissect the criminal act of money politics in terms of the norm structure. Method of the Research: this paper uses the method of statutory approach (statute approach), conceptual approach (conceptual approach) and philosophical approach to legal (philosophical approach). Results of the Research: norm structure can be divided into 4 (four) elements, namely norm subjects (normadressat), norm operators (modus van behoren), norm objects (normgedrag) and norm conditions (normconditie). The criminal act of money politics mentioned in this paper only revolves around the norms regulated in article 515 and article 519 of the Election Law. Basically the two articles have similarities in the subject elements of norms and norm operators. The subject of the norm of both articles is